Ultrasonic Tube Hydroforming, a New Method to Improve Formability. (2015) - Shahri, S.E. Eftekhari; Boroughani, S.Y. Ahmadi; Khalili, K.; Kang, B.S.
Abstract: In tube hydroforming process, due to friction condition, uniform wall thickness and sharp corners may not be achieved. Use of ultrasonic vibration can improve the contact conditions at the tube-die interface. The current work studies the effect of applying ultrasonic vibration on wall thickness and corner filling of hydroformed tubes. In order to understand the process an analytical model based on geometric relationships and stress-strain states has been established. The wall thickness and corner radius of hydroformed tube can be obtained by solving the model. By comparing the results of the FEM models of tube in two cases of ultrasonic hydroforming (internal pressure along with the oscillations of the die) and conventional hydroforming (internal pressure only), the effects of vibration on wall thickness and corner filling are investigated. The results indicate superimposing ultrasonic vibrations to the process will increase corner filling ratio of the tube significantly, and more uniform tube wall thickness will be achieved.